Composition and Antimicrobial Activity of Essential Oil from the Aerial Part of Artemisia annua - Li, Yan; Hu, Hao-Bin; Zheng, Xu-Dong; Zhu, Ji-hua; Liu, Li-Ping (Asian Journal of Chemistry, 2011)
Artemisia annua is widely used as key components of traditional Chinese medicine in China. The compositions of essential oil extracted by hydro distillation from the stem and spike of Artemisia annua were identified using GC/MS. The stem oil comprized of 50 components, while the spike oil contained 41 components. There were 30 same compounds. Twenty seven unreported compounds were b-pinene, b-phellandrene, citronellol, borneol, linalool and cuminic alcohol etc. The relative content of terpenoids from the spike oil was more than it from the stem oil, so the antimicrobial activity of the spike oil was more active than it of the stem oil. MICs of the essential oil of them were different from microorganisms.